2019
DOI: 10.1371/journal.pone.0214544
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vitro performance evaluation of resveratrol for oral self-microemulsion

Abstract: The purpose of this study was to improve the solubility of resveratrol (Res) by a self-microemulsifying drug-delivery system (SMEDDS). Through a solubility experiment, the pseudoternary phase diagram and ternary phase diagram were used to optimize the Res SMEDDS formula. The optimum formulation consisted of 5% IPM, 20% PEG400, and 65% Cremophor RH40. The water solubility, stability, in vitro release and antioxidant activity of the Res SMEDDS were characterized. The Res solubility in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Its suitability for the preparation of emulsions with either essential oils or antimicrobial agents for the therapy of wounds was also described ( 27 ). Apart from Labrasol, the review of the literature indicated that PEG 200, Cremophor RH 40, or Tween 80 could also be used as solvents for RSV ( 28 30 ). The solubility of RSV in these solvents was 30 mg/mL [RT], 150 mg/mL [37°C] or 80 mg/mL [37°C] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Its suitability for the preparation of emulsions with either essential oils or antimicrobial agents for the therapy of wounds was also described ( 27 ). Apart from Labrasol, the review of the literature indicated that PEG 200, Cremophor RH 40, or Tween 80 could also be used as solvents for RSV ( 28 30 ). The solubility of RSV in these solvents was 30 mg/mL [RT], 150 mg/mL [37°C] or 80 mg/mL [37°C] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Labrasol has been found to interact with tight junctions in the intestinal epithelium via an interface with F-actin and actin-anchoring proteins [26]. Furthermore, drug loading of 20 mg each of quercetin and resveratrol to this blank microemulsion was found to result in smaller droplet sizes than reported previously for the individual compound loading microemulsion [27]. This indicated that QR-SME possesses a greater surface area, which may promote the rate of quercetin and resveratrol release.…”
Section: Discussionmentioning
confidence: 64%
“…Type identification suggests that the OST-NE was O/W type ( Figure 3(c) ). Smaller droplets have a greater interfacial area that significantly enhances the release rate of the drug [ 50 ]. The particle size of OST-NE was small and uniform, with an average particle size of 22.33 ± 0.47 nm.…”
Section: Discussionmentioning
confidence: 99%